Developing Communicative Grammar Materials for Teaching Speaking in the Eleventh Grade at Alam Kudus Senior High School Bali. - Polin, Junias (Universitas Pendidikan Ganesha, 2018)
This study is aimed at finding out how need analysis is conducted for developing communicative grammar materials for teaching speaking in the eleventh grade of Kalam Kudus senior high school; how Communicative Grammar Materials developed; and analysing the quality of the developed Communicative Grammar Materials for teaching speaking skill in the eleventh grade. This study applied Research and Development design proposed by Sugiyono (2010) which simplified into six steps, and Borg and Gall (1983) model was adapted to do need analysis. The study found that the obtained need analysis were conducted through observation, questionnaire, document analysis, and interview. The Communicative Grammar materials were developed using criteria proposed by Leech (2013) that is designed based on Hutchinson and Waters (1987) by considering the basic competency and indicators in the KTSP 2006 syllabus used at school and they topics developed; (1) giving and asking for opinion, (2), Expressing satisfaction and dissatisfaction, (3) Giving advice and responding to advice, (4) Expressing warning and responding to warning, (5) Accepting Invitation, (6) Expressing feeling of relief, pain, and pleasure, (7) Expressing love, (8) Expressing sadness, (9) Expressing Embarrassment, (10) Expressing anger and annoyance. The product of this study follows good criteria of teaching material which proposed by Leech (2013) and The quality of the product perceived by the expert judges was in a good category that is shown in the criteria and interval of 229 (X=229) using Gregory (20l0) formula.